1980
DOI: 10.1038/286295a0
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein mRNA induction in HeLa cells in response to zinc or dexamethasone is a primary induction response

Abstract: Metallothioneins (MTs) are low molecular weight, heavy metal binding proteins unique in their high cysteine content and high affinity for Zn2+, Cd2+, Hg2+, Ag2+ and Cu2+ (refs 1--3). The synthesis of MTs is induced by zinc or cadmium in the liver and kidney and in cultured cells. More recently MT induction by the steroid hormone dexamethasone (Dex) has been demonstrated in HeLa cells and adrenalectomized rats. Because glucocorticoid hormones lead to an intracellular accumulation of zinc, the question arises of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
64
2

Year Published

1981
1981
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(76 citation statements)
references
References 20 publications
10
64
2
Order By: Relevance
“…Exposure to metals, organic chemicals, physical stress, intracellular damage, and physiologic agents causes an increase the steady-state level of MT mRNA (5,(37)(38)(39)(40). In addition, several of these nonmetal stressors activate MT transcription via MREs (10,22,41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to metals, organic chemicals, physical stress, intracellular damage, and physiologic agents causes an increase the steady-state level of MT mRNA (5,(37)(38)(39)(40). In addition, several of these nonmetal stressors activate MT transcription via MREs (10,22,41,42).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that mRNA induction by dexamethasone does not require de novo protein synthesis [36]. However it is not clear whether dexamethasone inhibition of mRNA induction requires de novo protein synthesis or not.…”
Section: ~Bmentioning
confidence: 99%
“…Reference Diesterhaft et al (1980), Olson et al (1980) Danesch et al (1983) Sarkar & Griffith (1976) McGinnis & de Vellis (1978) Chen & Feigelson (1979) Karin et al (1980), Mayo & Palmiter (1981) Mierendorf & Mueller (1982)…”
mentioning
confidence: 99%